2018
DOI: 10.1186/s12917-018-1567-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the apoptosis-related SH3RF1 and SH3RF2 genes and their association with exercise performance in Arabian horses

Abstract: BackgroundApoptosis plays an important role in the regulation of healthy tissue growth and development as well as in controlling the maintenance of homeostasis in exercising muscles. During an intensive physical effort, the regulation of cell death by apoptosis results in the replacement of unaccustomed muscle cells by new cells that are better suited to exercise. The aim of this study was to determine the expression of two genes (SH3FR1 and SH3RF2) that control apoptosis in muscle tissues during training peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This observation confirmed that long-term training is recognized by the organism as a stress factor and that such inflammatory responses can have an important function in triggering downstream signalling pathways, which are critical to homeostasis maintenance [19]. Whole gene expression modification in blood and muscle has allowed the proposal of a panel of genes ( PK3CG , FOXO3 , SLC16A1 , ME3 , ACTN3 , PPARa , SH3RF2 , TPM3 , TNNC1 , TNNI3 , TGFBR1 , TGFBR2 , and FABP3 ) potentially associated with flat racing performance in Arabian horses; these genes are currently being studied for use as markers for selection [23, 24].…”
Section: Transcriptomic and Mirnaomic Analyses Of Racing Performanmentioning
confidence: 99%
“…This observation confirmed that long-term training is recognized by the organism as a stress factor and that such inflammatory responses can have an important function in triggering downstream signalling pathways, which are critical to homeostasis maintenance [19]. Whole gene expression modification in blood and muscle has allowed the proposal of a panel of genes ( PK3CG , FOXO3 , SLC16A1 , ME3 , ACTN3 , PPARa , SH3RF2 , TPM3 , TNNC1 , TNNI3 , TGFBR1 , TGFBR2 , and FABP3 ) potentially associated with flat racing performance in Arabian horses; these genes are currently being studied for use as markers for selection [23, 24].…”
Section: Transcriptomic and Mirnaomic Analyses Of Racing Performanmentioning
confidence: 99%
“…It's worth to mention that molecular network of ACTN3 gene showed the direct association with SH3RF2 gene, described as cell anti-apoptotic factor. The previous studies have shown a signi cant downregulation of SH3RF2 during intensive physical effort, concluding that apoptosis leads to replacing damaged muscle bers by new, better suited to exercise [15]. As both SH3RF2 and ACTN3 genes could be potentially used as genetic markers of endurance predispositions in horses, their in uence at the molecular level can be assumed and may constitute the basis for further research.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, some genes (such as SH3RH2, TNNI2) (Fig. 4) belonged to KL -ACTN3 molecular network were identi ed previously as related to sport phenotype in horses [15,7] and in other mammals [16].…”
Section: Molecular Interaction Network Between Actn3 Kl and Most Rela...mentioning
confidence: 99%
“…The RNA-Seq method is widely used in searching for genetic determinants of performance in horses [2,4,5]. The global gene expression comparison of tissues sampled in different points during the training of Arabian horses allows for the marking of potential genes that, further validated, may act as potential markers of a wide range of traits [6,7]. In the present manuscript, we performed exact transcript abundance analysis in a gene previously significantly deregulated in the results of RNA-Seq analysis, in a panel of muscle and whole blood samples, for the investigation of its potential as a marker.…”
Section: Discussionmentioning
confidence: 99%
“…These findings led to further investigation and evaluation of RNA-Seq-based single nucleotide polymorphisms, located within the most significant deregulated differential expressed genes (DEGs), as potential markers for racing abilities in Arabian horses. The genes included SH3RF2 (SH3 domain containing ring finger 2) [6], ACTN3 (actinin alpha-3) [7], and SLC16A6 (monocarboxylate transporter 7) [8,9]. The search for blood-based markers related to performance traits holds interest for many researchers.…”
Section: Introductionmentioning
confidence: 99%